Practically observation of standard Minute Value of T-shirt (International Journal of Engineering and Computer Science, 2017)
This research project is based on calculation of standard minute value of T-shirt. An experimental investigation for the distribution of SMV for each and every operation require for making a T-shirt and provides a clear and details concepts for determining line balancing, machine requirements, man power allocation for setting a definite target within a reasonable efficiency. This project is a details discussion and distribution of SMV which will assist to minimize SMV by having a better synchronization with man, machine, materials and methods to achieve higher efficiency.